Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/sjme-05-2020-0086
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brand love on brand loyalty: the moderating role of self-esteem, and social influences

Abstract: Purpose The purpose of this paper is threefold. First, it aims to clarify the moderating role of self-esteem (SE) and susceptibility to normative influence (SNI) in the relationship between brand love and brand loyalty. Second, the study proposes modeling the mediation role of brand love and outlining how SE and SNI affect the consumer-brand relationship. Finally, the study explores the impact of brand love on brand loyalty: the moderating role of self-esteem and social influences, as the literature regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
67

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(123 citation statements)
references
References 154 publications
(211 reference statements)
1
55
0
67
Order By: Relevance
“…Adapun salah satu tolok ukur kesuksesan strategi bersaing dalam dalam konteks desa wisata adalah kemampuan pengelola untuk meningkat kepuasan dan loyalitas wisatawan (Alharbi et al, 2018). Loyalitas pembeli diukur dengan kemungkinan dan aktualitas pembelian berulang yang sama (Le, 2020). Loyalitas dibentuk karena adanya kepuasan pengguna produk, kualitas produk, kualitas layanan, dan harga produk yang wajar.…”
Section: Pandu Kusuma Jati Uswatun Chasanah Anas Hidayatunclassified
“…Adapun salah satu tolok ukur kesuksesan strategi bersaing dalam dalam konteks desa wisata adalah kemampuan pengelola untuk meningkat kepuasan dan loyalitas wisatawan (Alharbi et al, 2018). Loyalitas pembeli diukur dengan kemungkinan dan aktualitas pembelian berulang yang sama (Le, 2020). Loyalitas dibentuk karena adanya kepuasan pengguna produk, kualitas produk, kualitas layanan, dan harga produk yang wajar.…”
Section: Pandu Kusuma Jati Uswatun Chasanah Anas Hidayatunclassified
“…This strategic competitive resource trigger proved to be an effective tool to enhance brand gravity-resonance capability that strengthens brand love studies (Albert & Merunka, 2013;J. Khan et al, 2021;Kumar et al, 2021;Le, 2020;Shahid & Zafar, 2021). The logic behind this model that brand experience is the first step to improving capabilities echoes the brand's appeal to intangible entities that enable companies to generate valuable market offerings effectively and or efficiently.…”
Section: Conclusion and Recommen-dationmentioning
confidence: 94%
“…Many studies confirmed that increased participation and engagement on brand page can lead to brand loyalty (Kang, Tang & Fiore, 2014;Jayasingh, 2019). Also, other factors such as brand love, consumer and brand engagement, brand identification, and group characteristics were also found to influence brand loyalty (Kumar & Nayak, 2019;Le, 2021;Liao et al, 2020;Lin et al, 2019;Liu et al, 2019).…”
Section: 3mentioning
confidence: 94%